Effects of thermal aging on ductile-to-brittle transition temperature behavior of welded A516 steel - Khattak, M. A. (Trans Tech Publications, 2011)
Prolonged high temperature exposure of welded C-Mn steels is likely to cause microstructural changes leading to an inrease in the ductile-to-brittle transition temperature (DBTT) of the welded joint. Consequently, such degrading material properties should be quantified in view of establishing accurate component life prediction model. This study examined effects of isothermal aging on DBTT behavior of the heat affected zone (HAZ) in welded Type A516 Gr 70 steels. Microstructures of the as-received weld region revealed the presence of pearlite and ferrite in the base metal while upper and lower bainite are found in the HAZ and weld metal, respectively. Hardness measures for the weld metal region, HAZ and base steel are 172, 209 and 150, respectively. Aging at 420 °C, 500 hours lowers hardness value of the HAZ by 20 %. A series of Charpy impact tests on V-notched specimens are performed for as-received and thermally aged samples at 420 °C for 500, 800 and 1200 hours. Results showed that the absorbed impact energy displays a sigmoidal variation with test temperatures. DBTT ranges from -60 to 5 °C for HAZ while narrow range from -25 to 12 °C for weld metal region. Absorbed impact energy variations in samples aged for durations up to 800 hours display another saturation level over test temperatures between -30 to 10 °C. Fractographic analysis on HAZ fracture surface indicated brittle fracture at - 60 °C while ductile failure dominated at 27.7 °C. A mix-mode fracture mechanism is displayed for test conducted at -38 °C.